2013
DOI: 10.1111/trf.12195
|View full text |Cite
|
Sign up to set email alerts
|

Very‐short‐term perioperative intravenous iron administration and postoperative outcome in major orthopedic surgery: a pooled analysis of observational data from 2547 patients

Abstract: Despite known limitations of pooled observational analyses, these results suggest that very-short-term perioperative administration of IV iron, with or without rHuEPO, in major lower limb orthopedic procedures is associated with reduced ABT rates and LHS, without increasing postoperative morbidity or mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
144
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(153 citation statements)
references
References 49 publications
5
144
1
3
Order By: Relevance
“…No standard dose exists in this setting; however, total doses of 200 to 600 mg of iron sucrose (100-200 mg every 48 hours for 2-3 doses beginning on the day of admission) perioperatively have been reported in studies focusing on IV iron. [26][27][28][29][30][31] Studies typically did not report baseline iron labs; however, 1 trial specified that patients had nearnormal iron levels (46.3-53.2 µg/dL), with no significant difference between groups as well as normal ferritin and transferrin levels. 26 No difference has been shown in blood transfusion rates (percentage of patients receiving a transfusion) in studies that compared patients receiving IV iron alone administered throughout the preoperative and postoperative periods with patients not receiving iron.…”
Section: Perioperative Settingmentioning
confidence: 99%
“…No standard dose exists in this setting; however, total doses of 200 to 600 mg of iron sucrose (100-200 mg every 48 hours for 2-3 doses beginning on the day of admission) perioperatively have been reported in studies focusing on IV iron. [26][27][28][29][30][31] Studies typically did not report baseline iron labs; however, 1 trial specified that patients had nearnormal iron levels (46.3-53.2 µg/dL), with no significant difference between groups as well as normal ferritin and transferrin levels. 26 No difference has been shown in blood transfusion rates (percentage of patients receiving a transfusion) in studies that compared patients receiving IV iron alone administered throughout the preoperative and postoperative periods with patients not receiving iron.…”
Section: Perioperative Settingmentioning
confidence: 99%
“…Over 70% of anemic patients presented with ID or functional ID (FID), resulting in iron-restricted erythropoiesis (IRE) [7]. As for nonelective procedures, up to 75% of patients undergoing hip fracture repair surgery ( n = 1,004) presented with Hb <13 g/dL on admission [8]. …”
Section: Prevalence and Consequences Of Perioperative Anemiamentioning
confidence: 99%
“…For adults, transplantation using two cord units is frequently necessary [3][4][5] and literature demonstrates that double umbilical cord blood transplantation (DUCT) yields durable remissions [1,5,6]. Data on DUCT in hepatosplenic gamma-delta T-cell lymphoma with hemophagocytic lymphohistiocytosis (HLH) are limited to case reports [7,8]. We describe a 22-year-old woman with hepatosplenic gamma-delta lymphoma with hemophagocytosis treated with DUCT.…”
Section: Author Contributionsmentioning
confidence: 99%
“…In a pooled analysis of 2,547 perioperative patients who underwent either hip fracture repair or lower limb arthroplasty, Munoz et al reported a decrement in transfusion rate from 48.8 to 32.4% in those who received perioperative intravenous iron versus those who did not [7]. Postoperative infections were reduced from 26.9 to 10.7%, length of stay from 13.4 to 11.9 days and remarkably thirty day mortality from 9.4 to 4.8% in the IV iron group.…”
mentioning
confidence: 99%